Thermal behavior, powder X-ray diffraction, DFT calculations and vibrational spectra of barium bis(pentacyanonitrosylchromate) octahydrate, Ba3[Cr(CN)5NO]2·8H2O(D2O) - Soria, Delia Beatriz (2010)
The cell parameters of Ba3[Cr(CN)5NO]2·8H2O were determined from powder X-ray diffraction using the autoindexing program TREOR, and refined by the Le Bail methods with the FULLPROF program. An orthorhombic cell was determined with cell parameters a = 15.0324(2) Å, b = 12.9542(9) Å, and c = 7.5094(5) Å. Two possible space groups are consistent with the systematic absences: Pmcb (#55) and P2cb (#32). Infrared spectra are reported for the polycrystalline compound, isotopically normal and partially deuterated, at temperatures ranging between ca. 80 K and 293 K together with the room temperature Raman spectrum. The assignment of the observed bands was accomplished assuming the existence of one type of pentacyanonitrosylchromate ion in the asymmetric unit, as suggested by the single band found in the NO stretching region of the deuterated anion and in the anhydrous compound. TGA-DTA data are also reported and discussed. The assignments are supported by DFT calculations of the normal modes of vibration of the [Cr(CN)5NO]3− structure, optimized at the same level of theory.